The effect of El Bernameg TV show on Egyptian young viewers’ evaluation of Egyptian media figures - Kadry, Menna Mohamed (AUC Knowledge Fountain, 2016)
The study examines the impact of Egyptian political satire show, El Bernameg, upon young Egyptian viewers’ evaluation of Egyptian media figures. The significance of researching this topic comes from being the first of its kind in Egypt, combining both comedy and political discussions. In the form of a mock commentary, the program has tackled as well as lampooned a variety of political topics and public figures ranging from presidential candidates to government officials to media figures and even entertainers. The study particularly focused on the potential impact of El Bernameg’s metacoverage upon young Egyptian viewers, mainly when it comes to evaluating the role of prominent Egyptian media figures.